The Anatomy of Governance Breakdown: Rethinking Authority and Regulation in Fragile Contexts - Abdulrauf Atia; Entisar Alatrish (LAW & PASS: International Journal of Law, Public Administration and Social Studies, 2026)
Contemporary governance is increasingly challenged by conditions of fragility, instability, and institutional fragmentation. This article examines governance breakdown as a multidimensional phenomenon that extends beyond institutional failure, focusing on the interplay between authority, regulation, and social legitimacy in fragile contexts. Using a qualitative and conceptual approach grounded in interdisciplinary literature, the study explores how governance systems operate when state authority is fragmented, legal frameworks are pluralistic, and administrative practices are weakened. The findings reveal that governance breakdown is characterized by overlapping and competing sources of authority, disrupted regulatory coherence, contested social values, and ineffective administrative mechanisms. Rather than indicating the absence of governance, these conditions reflect a reconfiguration of governance processes under structural constraints. The study contributes to the literature by reconceptualizing governance breakdown as an analytical framework for understanding the limits of conventional governance models. It highlights that effective governance depends not only on formal legal structures but also on their alignment with social legitimacy and their implementation through functional administrative practices. The article further emphasizes the need for adaptive, context-sensitive governance approaches capable of addressing normative diversity and institutional complexity in fragile environments.